Reduction in Serum High-Sensitivity C-Reactive Protein Favors Kidney Outcomes in Patients with Impaired Fasting Glucose or Diabetes - Lili Liu; Bixia Gao; Jinwei Wang; Chao Yang; Shouling Wu; Yuntao Wu; Shuohua Chen; Qiuyun Li; Huifen Zhang; Guodong Wang; Min Chen; Ming-hui Zhao; et al. (Journal of Diabetes Research)
Objective. We aimed to evaluate whether the reduction in serum high-sensitivity C-reactive protein (hs-CRP) favors kidney outcomes. Methods. This study was a subanalysis including patients with impaired fasting glucose or diabetes of the Kailuan cohort study. The predictor was based on two consecutive visits of hs-CRP levels in 2006 and 2008. A total of 3924 patients with hs-CRP≥3 mg/L in 2006 were divided into two groups according to whether the levels of hs-CRP were reduced in 2008: Group 1: no reduction: hs-CRP≥3 mg/L in 2008; Group 2: reduction: hs-CRP<3 mg/L in 2008. Kidney outcomes include kidney function decline and development and progression of proteinuria and were followed up until the end of 2015. Results. There were 3905, 2049, and 493 patients included into our analysis for the outcomes of kidney function decline and the development and progression of proteinuria, respectively. A total of 398, 297, and 47 events occurred after 5 years of follow-up, respectively. Cox regression revealed that patients with reduction in hs-CRP have lower risk of kidney function decline (HR 0.71, 95% CI 0.57-0.89, and P=0.002) and development of proteinuria (0.77, 0.61-0.99, and P=0.038) after controlling for potential confounders as compared to those with no reduction in hs-CRP levels. Conclusions. Reduction in serum hs-CRP levels favors kidney outcomes in patients with impaired fasting glucose or diabetes.